2017
DOI: 10.14814/phy2.13142
|View full text |Cite
|
Sign up to set email alerts
|

Hemodynamic responses are reduced with aerobic compared with resistance blood flow restriction exercise

Abstract: The hemodynamics of light‐load exercise with an applied blood‐flow restriction (BFR) have not been extensively compared between light‐intensity, BFR, and high‐intensity forms of both resistance and aerobic exercise in the same participant population. Therefore, the purpose of this study was to use a randomized crossover design to examine the hemodynamic responses to resistance and aerobic BFR exercise in comparison with a common high‐intensity and light‐intensity non‐BFR exercise. On separate occasions partici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
47
1
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(55 citation statements)
references
References 30 publications
(112 reference statements)
5
47
1
2
Order By: Relevance
“…For example, Polito et al (2007) demonstrated similar blood pressure responses between heavy weights training with few repetitions compared with lighter weights training for more repetitions. Importantly, LL BFR resulted in elevated blood pressures when compared with LL and HL, findings similar to those previously reported for older hypertensive ( Pinto and Polito, 2016 ) and normotensive ( Vieira et al, 2013 ; Sardeli et al, 2017 ) individuals, as well as for healthy young men ( May et al, 2017 ). These findings have practical relevance for practitioners, especially if they are considering the implementation of BFR training in hypertensive patients.…”
Section: Discussionsupporting
confidence: 89%
“…For example, Polito et al (2007) demonstrated similar blood pressure responses between heavy weights training with few repetitions compared with lighter weights training for more repetitions. Importantly, LL BFR resulted in elevated blood pressures when compared with LL and HL, findings similar to those previously reported for older hypertensive ( Pinto and Polito, 2016 ) and normotensive ( Vieira et al, 2013 ; Sardeli et al, 2017 ) individuals, as well as for healthy young men ( May et al, 2017 ). These findings have practical relevance for practitioners, especially if they are considering the implementation of BFR training in hypertensive patients.…”
Section: Discussionsupporting
confidence: 89%
“…The RPE was larger in 40LL+BFR than in 40LL but was not different from 70HL. Similar results were obtained when comparing high-load exercise with low-load exercise with BFR 14 . However, in the study of May, Brandner, Warmington 14 lower RPE was observed when the exercise was performed with BFR compared to a high-load session., The authors utilized an intermittent protocol (4 sets of 2 minutes) and lower intensities of walking (4 km/h).…”
Section: Discussionsupporting
confidence: 84%
“…It has been reported that combining BFR with aerobic exercise improves VO2max 9,10 and promotes similar gains in muscle strength and hypertrophy to high-load exercise in young healthy men 11 . Furthermore, several studies compared the acute responses of HR and RPE during resistance 12,13 and aerobic exercise 14 and verified equal or lower hemodynamic responses during or after exercise when performed with BFR compared to high-load exercise without BFR. Additionally, in the study of Ferreira, et al 15 , lower hemodynamic responses and improvement in time and frequency domain indices of HRV were verified during recovery from low-load aerobic exercise with BFR compared to a high-load session in elderly participants.…”
Section: Introductionmentioning
confidence: 95%
“…In the BFR-RE literature, a common and frequently used set and repetition scheme exists that involves 75 repetitions across four sets of exercises, with 30 repetitions in the first set and 15 repetitions in each subsequent set (Yasuda et al, 2006, 2010a,b, 2011a,b, 2012; Madarame et al, 2008; Rossow et al, 2012; Ozaki et al, 2013; Loenneke et al, 2016; May et al, 2017). It is also common to complete 3–5 sets to concentric failure during BFR-RE (Takarada et al, 2002; Cook et al, 2007, 2013; Loenneke et al, 2012a; Manini et al, 2012; Nielsen et al, 2012; Ogasawara et al, 2013; Fahs et al, 2015).…”
Section: Application Of Bfrmentioning
confidence: 99%
“…The effect of BFR-RE on the central cardiovascular response is dependent upon the level of BFR (Rossow et al, 2012), mode of exercise (i.e., BFR-RE vs. BFR-AE) (Staunton et al, 2015) and mode of application (i.e., continuous vs. intermittent BFR) (Brandner et al, 2015; Neto et al, 2016). BFR acutely affects central hemodynamic parameters when it is combined with RT (Takano et al, 2005; Rossow et al, 2011, 2012; Fahs et al, 2012; Vieira et al, 2013; Downs et al, 2014; Brandner et al, 2015; Staunton et al, 2015; Neto et al, 2016; Poton and Polito, 2016; Libardi et al, 2017; May et al, 2017), AE (Renzi et al, 2010; Kumagai et al, 2012; Sugawara et al, 2015; Staunton et al, 2015; May et al, 2017) or even in the absence of exercise (Iida et al, 2007). Whilst there is an increase in the central cardiovascular response during exercise, this returns to baseline acutely (5–10 min) post-exercise cessation.…”
Section: Application Of Bfrmentioning
confidence: 99%